A systematic scoping review and textual narrative synthesis of long-term health-related quality of life outcomes for adolescent idiopathic scoliosis. (February 2021) - Essex, Ryan; Bruce, Gemma; Dibley, Molly; Newton, Paul; Dibley, Lesley
Abstract: Introduction: Idiopathic scoliosis is a musculoskeletal condition leading to deformity of the spinal column. There is strong evidence reporting short term health-related quality of life outcomes, but less is known about the longer-term impact of adolescent idiopathic scoliosis (AIS). This paper reports the current evidence on long-term non-clinical outcomes of AIS. Method: A systematic scoping literature review combining descriptive and textual narrative synthesis was undertaken. Studies were included if they: sampled or followed up participants at least 10 years after diagnosis and/or treatment, contained health-related quality of life data that could be extracted, where the intervention (or diagnosis in the case of untreated) occurred after 1980, and where data was extractable for modern rod and screw or fusion techniques, non-surgical interventions or untreated patients. Results: Twenty-three studies were included. Overall, the HRQOL measures utilised by these studies suggest that HRQOL is not related to participant demographics or AIS characteristics or type or extent of surgical intervention. Some studies suggest that those with AIS scored worse than controls. Discussion: Results suggest that AIS participants had a generally good quality of life, although this was often worse than those without AIS. No other clear relationships were found. The available literature fails to address more fundamental questions about how HRQOL is conceptualised for those with AIS, and there is value in pursuing qualitative inquiry in this area.